AN ANALYSIS OF USING CODE MIXING FOUND IN THE FEMINA MAGAZINE - I Made Juliarta; Putu Eka Suardana (Merwinspy Publisher, 2023)
This research focuses on code mixing found in the femina magazine. The objective of this research was to find out the types and levels of code mixing found in the femina magazine. Intra-sentential code mixing is called as the appearance of a phrase, clause, or a sentence boundary in the utterance of someone This research applied descriptive qualitative methodand the human research is the main instrument of this research. In method of collecting the data, this research applied documentation method. This study applied content analysis that focused on analyzing the types of code mixing which defined by Hoffman and the levels of code mixing that argued by Suwito. Intra sentential code mixing in the form of word and phrase are found in the data source. There were 9 data of intra sentential code mixing in the form of word found in the data source. And there were 9 data of intra sentential code mixing in the form of phrases that were found in the data source.